Stability of strain genotypes of Burkholderia pseudomallei from patients with single and recurrent episodes of melioidosis. - Vadivelu, J.; Puthucheary, S.D.; Drasar, B.S.; Dance, D.A.; Pitt, T.L. (Wiley, 1998)
The constancy of strain genotypes of multiple isolates of Burkholderia pseudomallei from 13 patients with melioidosis was examined by BamHI ribotyping and pulsed-field gel electrophoresis (PFGE) of XbaI digests of DNA. Seven of 8 patients with single episodes of melioidosis each yielded genetically identical isolates and only one of five patients with recurrent episodes was infected with a new strain clearly distinct from the original primary strain. Variation was observed in PFGE patterns of primary and relapse isolates of another patient but this was insufficient to define genetically distinct strains. We conclude that most patients with single or multiple episodes of melioidosis retain a single strain.